The influence of the sexual habit and the risk of infection for HIV: knowledge of univeristy recently-entrances in UFAC, year 1999 - Gadelha, Luciano M.; Lopes, Creso M. (Brazilian Journal of Sexually Transmitted Diseases, 2000)
The realized studying 550 closc 10 76.9% students recently-entances in the 21 courses oí lhe Federal University of Acre the year of 1999. with the objectivc of verifying the knowledege of ihe influence of the sexual habil and the risk of acquiring DST’s/ Aids. For the collection of data il has becn mnde use of a Scalc of Liken, adapted of Gir. Moriya e Figueiredo (1994). which consisted of identification data and 25 subjects tuming on the sexual practice. These subjects were contained in 7 factors one that was not included as factor. The answers of the scale 10 the socres +3 and +2 were considered of High Risk. The one +I, 0 e - 1 of Mediurn Risk and -2 -3 as of Low Risk. The results demonstrated that: 55.6% were of the feminine gender. 44.491- of the masculine 42.4% were in lhe 20-24 year-old age group, 30.6% in thc one of 17- 19 years. while 74.2% single and 18.9% rnurricd. For the Oral Sex. the Promiscuous Sex and lhe Sex with Penetration the answers of the Unyversity Students from Acre. Went to the High Risk. For its time the Sex with Preservative, at the Mouth 10 Mouth Contact and the hand Estimulating, the answers went 10 the Mediun Risk. For its time, 10 Selí-Estirnulaling obtained answer for the Low Risk. while last 10 the not lncluded items as Factors the answers went to High Risk.